(untitled) (American Economist: Journal of Economics Finance and Global Policy, 2026)
This study examines the theoretical and managerial foundations for the sustainable development of tourism in transboundary regions, using the Republic of Karakalpakstan as a case study. The research identifies key challenges associated with ecological vulnerability, cross-border dynamics, and institutional coordination. A conceptual management framework is proposed to enhance sustainable tourism governance. The study applies mixed methods, including comparative analysis, statistical review, and system modeling. Results demonstrate that integrated governance, ecological prioritization, and cross-border cooperation significantly improve tourism sustainability. The findings contribute to regional development theory and offer practical recommendations for policymakers